University-School Partnerships: on the impact on students of Summer Schools (for school students aged 17-18) run by Bristol ChemLabS - GRAYSON, DAVID (Babes-Bolyai University, 2010)
Chemistry summer schools for 17-18 year old school students in the UK were run by Bristol ChemLabS, a Centre for Excellence in Teaching and Learning in Chemistry at the University of Bristol. Students attending were all studying Chemistry at post-16 level (A level in the UK) and experienced not only new practical techniques but also lectures on cutting-edge science as well as interacting with postgraduate role models. The students completed pre and post summer school questionnaires to ascertain the impact of the summer school on them. Paired t-tests were used to ascertain significant changes at the 2? level. There was no significant difference observed for self-concepts in Chemistry and Mathematics. For creative self-concept there was a significant increase (1?) for females but not males and a significant increase in academic selfconcept for the whole cohort. There was a high level of enjoyment of the summer school. There were a range of reasons for students attending the summer school and the benefits they produced and these are discussed. Interestingly, one of the main reasons for attending was to help students make choices of subject to study at University; however, the summer school opened the students? eyes to more possibilities rather than narrow the choices open to them.
PUBLISHED
Keywords: Education; Chemistry